XIth International Congress on Thrombosis and Haemostasis 1987
DOI: 10.1055/s-0038-1644771
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Factor Viii and Von Willebrand Factor

Abstract: Factor VIII (FVIII) circulates in plasma as a non-covalent complex with von Willebrand factor (VWF), a large multimeric adhesive glycoprotein. VWF serves as a carrier for FVIII and is thought to stabilize FVIII. The interaction between the two proteins was studied by binding purified human 125I-FVIII to VWF which was coated on a solid matrix. Experiments employing isolated heavy and light chains of FVIII and monoclonal antibodies indicated that binding occurred through the carboxyterminal 80kDa light chain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The addi tion of purified vWF appeared to increase the potency of the purified concentrates when assayed with the Diagen immunode pleted plasma (fig. 2); this could be due to enhanced stability of factor VIII:C in the presence of excess vWF, since it has been shown that vWF protects factor VIII:C from degradation by activated protein C [14]. These results, if confirmed, suggest that plas mas which have been immunodepleted of vWF may be unsuitable for assay of highly purified factor VIII.…”
Section: Discussionmentioning
confidence: 60%
“…The addi tion of purified vWF appeared to increase the potency of the purified concentrates when assayed with the Diagen immunode pleted plasma (fig. 2); this could be due to enhanced stability of factor VIII:C in the presence of excess vWF, since it has been shown that vWF protects factor VIII:C from degradation by activated protein C [14]. These results, if confirmed, suggest that plas mas which have been immunodepleted of vWF may be unsuitable for assay of highly purified factor VIII.…”
Section: Discussionmentioning
confidence: 60%
“…Plasma FVIII is maximally stabilized when it circulates in a noncovalent complex with vWf [11, 12]. In vitro , vWf appears to protect FVIII from activation by factor Xa [13], from inactivation by activated protein C [14], and to prevent FVIII from binding to phospholipids [15] and activated platelets [16]. In vivo , FVIII has a normal intravascular survival only when complexed to vWf, which not only preserves FVIII integrity but also may selectively concentrate FVIII at sites of vascular injury [16].…”
Section: Introductionmentioning
confidence: 99%
“…Its function in plasma remains to be elucidated. The presence of the RGD tripeptide indi cates that it may interact with other proteins, such as cell surface receptors [48], Further more, it has been suggested that pro-poly peptide in plasma, as part of pro-vWF, stabi lizes factor VIII [49], Although a factor VIII binding domain on mature vWF is localized within the First N-terminal 272 amino acid residues (D' domain and part of D3), this suggestion can formally not be excluded as yet [93][94][95].…”
Section: Biosynthesis Of Vwf By Human Endothelial Cellsmentioning
confidence: 99%